Atypical pantothenate kinase-associated neurodegeneration with variable phenotypes in an Egyptian family - Shalash, Ali S.; Rösler, Thomas W.; Abdelrahman, Ibrahim Y.; Abulmakarem, Hatem S.; Müller, Stefanie H.; Hopfner, Franziska; Kuhlenbäumer, Gregor; Höglinger, Günter U.; Salama, Mohamed (Heliyon, 2021)
Pantothenate kinase-associated neurodegeneration (PKAN) is a rare hereditary neurodegenerative disease characterized by an accumulation of iron within the brain. In the present report, we describe a family with 4 affected siblings presenting with variable clinical manifestations, e.g., parkinsonian features, dystonia and slow disease progression over 5 years. Exome sequencing revealed a causative variant in the pantothenate kinase 2 gene (PANK2). Variant NM_024960.6:c.710C > T was homozygous in all affected subjects. Our report describes the first genetically confirmed cases of PKAN in the Egyptian population. Studying genetics of neurodegenerative diseases in different ethnicities is very important for determining clinical phenotypes and understanding pathomechanisms of these diseases. Pantothenate kinase-associated neurodegeneration; PANK2; Neurodegeneration iron accumulation; Genetics.